O-254 Oral dydrogesterone (OD) versus micronized vaginal progesterone (MVP) for luteal phase support (LPS): impact on endometrium and genital tract microbiota. (30th June 2022) - Mackens, S; Olsen, C; Centelles-Lodeiro, J; Illingworth, K; Brucker, M. De; Boudry, L; Tournaye, H; Raes, J; Vieira-Silva, S; Blockeel, C
Abstract: Study question: Is there a difference in the endometrial transcriptome and/or reproductive tract microbiota composition when OD versus MVP is used as LPS for fresh embryo transfer? Summary answer: Endometrial transcriptome signatures and microbiota composition at the vaginal, cervical or intra-uterine site presented no significant differences following OD versus MVP. What is known already: Adequate LPS is crucial to achieve a successful pregnancy following ovarian stimulation (OS) and fresh embryo transfer. OD has been proven to be non-inferior compared to MVP in two phase III clinical RCTs. Additionally, a combined individual participant data and aggregate data meta-analysis showed an odds ratio in favor of OD for live birth. Little information is available on the potential differences at the molecular level of the reproductive organs following the administration of either LPS strategies. Given the potential immunomodulating properties of OD, of main interest is the endometrial functionality and microbiota composition of the female genital tract. Study design, size, duration: Thirty oocyte donors were planned to have two OS-cycles followed by one week of LPS (OD or MVP) in a randomized, cross-over, double-blind, double-dummy fashion. An endometrial biopsy, as well as vaginal/cervical/intra-uterine samples were collected. Endometrial RNA-sequencing was performed, raw reads were processed using STAR/htseq-count, differential gene expression was evaluated with EdgeR. Microbiota profiles were obtained by 16S-rRNA-sequencing using the DADA2-pipeline with RDP-classifier. Comparative analysis of genera relative abundances was performed in R. Participants/materials, setting, methods: All oocyte donors were <35 years old, had regular menstrual cycles, no intra-uterine contraceptive device, AMH within normal range and BMI≤ 29 kg/m 2 . OS was performed in a GnRH antagonist protocol followed by dual triggering (1000U hCG + 0.2mg triptorelin) as soon as ≥ 3 follicles of 20mm were present. Following oocyte retrieval, subjects initiated LPS consisting of MVP 200 mg (Utrogestan®) or OD 10 mg (Duphaston®), both three times daily. Main results and the role of chance: Subject and stimulation characteristics were comparable between the groups. For endometrial RNA-sequencing, 21 pairs (n = 42 biopsies) were available with the same oocyte donor having a biopsy after OD as well as after MVP (the remaining 9 subjects were excluded due to late follicular progesterone elevation/drop-out after one cycle). After correction for multiple hypothesis testing, no differentially expressed genes could be withheld and the principal component analysis plot showed one mixed OD/MVP cluster (PCA1 25% variance, PCA2 16% variance). The average Euclidean distance between samples of the OD group was significantly lower than for the MVP group (respectively 12.1 vs 18.8, comparison of the two-group wise Euclidean distributions results in p = 6.98e-14 using the Mann-Whitney test). Microbiota profiling was performed before and after OD/MVP (4 collections per subject). Samples with insufficient high-quality reads were excluded, resulting in 42 intra-uterine samplings, 82 cervical and 84 vaginal swabs used for analysis. No difference was seen at any site of the female reproductive tract following OD versus MVP in microbiota diversity, richness, genera abundances (delta contrasts [Mann–Whitney U test], padj > 0.1),  nor community composition (dbRDA genus-level Euclidean distances in vagina [R 2 = 0.22%, padj=0.26], cervix [R 2 = 0.36%, padj=0.20], uterus [R 2 = -0.06%, padj=0.45]). Limitations, reasons for caution: Sample size was limited. Whole tissue endometrial transcriptomics was performed on individual biopsies without accounting for the potential bias of different tissue compartment compositions among biopsies. As it was a double blind, double dummy study design, the impact of not administering medication via the vaginal route could not be evaluated. Wider implications of the findings: This is the first molecular study comparing OD/MVP. Results show that there is no difference between OD/MVP's ability to give rise to the receptive state, which corresponds with the clinical trial data. As the inter-sample distance of RNA-profiles was smaller following OD, interindividual variations could be lower for this approach. Trial registration number: EUDRACT 2018-000105-23